2018
DOI: 10.1016/j.regsciurbeco.2017.04.007
|View full text |Cite
|
Sign up to set email alerts
|

The more the merrier? Migration and convergence among European regions

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 40 publications
2
12
0
Order By: Relevance
“…To address this spatial interplay we adopt a methodology originally suggested by Kelejian and Prucha (, ), refined by Drukker, Egger, and Prucha () and Yang and Lee (), and applied by Jeanty, Partridge, and Irwin () in a study of migration and housing values, Fischer and Pfaffermayr () to explore migration and regional income convergence across Europe, and Delgado‐García, de Quevedo‐Puente, and Blanco‐Mazagatos () to study how the reputation of Spanish cities influence economic performance. Modified versions of the method have been adopted by Wu and Gopinath () in a study of spatial disparities in rural US economic development, as well as Cochrane, Grimes, and McCann, P.,& Poot, J.…”
Section: Models and Methodsmentioning
confidence: 99%
“…To address this spatial interplay we adopt a methodology originally suggested by Kelejian and Prucha (, ), refined by Drukker, Egger, and Prucha () and Yang and Lee (), and applied by Jeanty, Partridge, and Irwin () in a study of migration and housing values, Fischer and Pfaffermayr () to explore migration and regional income convergence across Europe, and Delgado‐García, de Quevedo‐Puente, and Blanco‐Mazagatos () to study how the reputation of Spanish cities influence economic performance. Modified versions of the method have been adopted by Wu and Gopinath () in a study of spatial disparities in rural US economic development, as well as Cochrane, Grimes, and McCann, P.,& Poot, J.…”
Section: Models and Methodsmentioning
confidence: 99%
“…But in contrast to the United States where mobility rates have been falling, the EU trend is less clear, and mobility may have been increasing (EU Commission 2018). Fischer and Pfaffermayr (2018) suggests that labor mobility plays a small role in reducing EU disparities in percapita GDP. Unfortunately, this increased mobility took place against a background of increasing concentration of economic activity and sorting of the high skilled toward big cities.…”
Section: Mobility and Spatial Disparitiesmentioning
confidence: 99%
“…On regional income growth rates, Barro and Sala-i Martin (1992) in one of the most-cited contributions on this topic, conclude that 'we showed that exogenous changes in migration seem to be unimportant in explaining the process of interregional convergence' (p. 28). Fischer and Pfaffermayr (2017), though, find accelerated -convergence across European NUTS 2 regions through migration. Looking again at regions within particular countries, Fratesi and Riggi (2007) find that similar to unemployment, migration increases disparities regarding income per capita in Italian regions.…”
Section: Introductionmentioning
confidence: 86%